Pembukuan dalam Perspektif Islam Studi Kasus Pembukuan Bagi Wirausaha Pemula Ibu Rumah Tangga Desa Kenongo - Masruchin Masruchin; Fitri Nur Latifah; M Ruslianoor Maika (Universitas Muhammadiyah Sidoarjo, 2017)
In accordance with the purpose of Sidoarjo District as the city of Indonesian SMEs, the government of Sidoarjo regency fierce empower SMEs and also creating new entrepreneurs in Sidoarjo. We assess with jealous people creating new businesses to supplement the family income, especially housewives should be appreciated properly. Obstacles often faced by new entrepreneurs are not have a good knowledge of the methods of recording finance both the cost of raw materials, operating costs, gain and losses. Not infrequently, the money that had been due to run out mixed business purposes or used for the needs of the family shopping. For that we want to provide training and mentoring for the housewife as new entrepreneurs especially in rural Kenongo to be able to make a simple bookkeeping for his business transactions. In the end, we hope that the additional knowledge of recording financial transactions, the housewife are able to get increased revenues and able to raise their business.